2014
DOI: 10.1111/iwj.12318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of vacuum‐assisted closure in patients with wound complications following tumour surgery

Abstract: Covering the reconstructed area with a healthy soft-tissue envelope is a major challenge after limb-sparing surgery in patients with malignant bone and soft-tissue tumours. Negative pressure wound therapy (NPWT) of open wounds hastens healing and minimises the requirement for complex reconstructive soft-tissue surgery. The aim of this study was to investigate the effectiveness and safety of NPWT in bone and soft-tissue malignant tumour patients with postoperative wound complications. Between January 2006 and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
7
0
3
Order By: Relevance
“…15,16 However, there is still a lack of good quality randomized studies free from conflicts of interest that would allow the method to be evaluated more thoroughly. 17 Complications that have been described in relation to vacuum dressings are uncommon and the majority are related to local pain, hypertrophy of granulation tissue, and damage to adjacent blood vessels. 18,19 It should however be stressed that the dressing foam should not be placed in direct contact with blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 However, there is still a lack of good quality randomized studies free from conflicts of interest that would allow the method to be evaluated more thoroughly. 17 Complications that have been described in relation to vacuum dressings are uncommon and the majority are related to local pain, hypertrophy of granulation tissue, and damage to adjacent blood vessels. 18,19 It should however be stressed that the dressing foam should not be placed in direct contact with blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The main doubt is the potentially angiogenic effect which can aggravate malignancy or recurrence of the cancer. 8 On the other hand, in last years some cases of using NPWT in the treatment of patients with malignant tumors has been observed. There are two main oncological groups of patients with malignancy and indication for NPWT.…”
Section: Discussionmentioning
confidence: 99%
“…2 There are only few contraindications for the negative pressure wound therapy use (e.g. an active malignant process, 3 however, it is reported that in some cases it has achieved positive effects [4][5][6][7][8][9][10] ).…”
Section: Introductionmentioning
confidence: 99%
“…Согласно данным доступной литературы факт применения различных средств и методик, созда-ющих отрицательное давление в ране, не является новшеством, однако использование стандартизи-рованных вакуумов для этих целей началось срав-нительно недавно [8,9]. В систематических обзорах [10,11,12] показана эффективность вакуум-терапии в отношении скорости репарации раневых повер-хностей различной этиологии.…”
Section: результаты и их обсуждениеunclassified
“…Однако масштабные исследования, свободные от конфликтов коммер-ческих интересов, которые бы позволили объектив-но оценить эффективность метода, по-прежнему отсутствуют [8]. В этой связи основной целью дан-ного исследования послужила оценка ранних ре-зультатов вакуум-терапии в комплексном лечении гнойно-некротических ран.…”
Section: Introductionunclassified